Closing the gates? Evidence from a natural experiment on physicians' sickness certification - Simen Markussen (University of Oslo, Department of Economics, 2009)
This paper exploits a Norwegian physician directed reform aimed to reduce sick-leave. Physicians were required to consider part-time sick-leave as the default treatment and - in the case of long lasting full-time sick-leave - to file a report documenting why the worker was unable to perform any work related activities. The reform had a large impact, reducing sick-leave by 18.8 percent. The main effect came from reduced spell duration - which can be directly linked to the extended documentation requirement laid on physicians within the first 8 weeks of a sick-leave spell. Physician-directed policies may be an (cost-) effective way of reducing sick-leave.
Keywords: H53; I18; J28; 330; Labor market policies; sick-leave; physicians' gate keeping; Arbeitsmarktpolitik; Fehlzeit; Krankheit; Teilzeitarbeit; Wirkungsanalyse; Norwegen